Dirigentes públicos, política e gestão: o sistema de alta direção pública chileno - Alessio, Maria Fernanda (2013)
This thesis discusses the public managers, actors recently considered by literature as a specific group, which is defined for being results-oriented and for pursuing public value creation. In general, there are few studies which discuss public managers empirically, so this work will show the roles they play arguing that these actors are central to the formulation and implementation process of public policy since they are capable to dialogue with both political and management spheres. For this, we will analyze the Chilean experience, a well-established system that recognizes the public managers as distinct actors from others – like bureaucrats or politicians –, governed by specific rules of recruitment, selection, nomination and management according to performance agreements. We present an analysis of the Chilean public managers based on both a historical perspective on the emergence and consolidation of its unique Senior Civil Service and in relation to the tensions and complementarities observed between technocrats and politicians in the Chilean government during the period covered, which is since (new) democratization until the current days. We show that the Senior Civil Service comes in the context of a political agreement between government and opposition in pursuit of State modernization and professionalization, and that the politics and management dimensions are central pillars of this model, existing in all its spheres, such as its design and institutional arrangements for managing people and performance.